Pengaruh Model Inquiry Terhadap HOTS Siswa SD - Hayu Puspita; Diyan Marlina; Fida Rahmantika Hadi (Prosiding Konferensi Ilmiah Dasar, 2022)
This study aims to determine the effect of the inquiry learning model on the HOTS of fourth grade students at MIN 2 Ponorogo. This research is a quantitative type of research with a quasi-experimental design method with a nonequivalent control group design. The population of this research is fourth grade students of MIN in Sukorejo district which consists of 180 students. The sample in this study were fourth grade students at MIN 2 Ponorogo which consisted of 21 students as the experimental class and 21 students as the control class. The sampling technique in this research is to use simple random sampling. Data collection techniques using tests and documentation. The data analysis technique in this research is a feasibility test of research questions which includes instrument validity and reliability tests and there is data analysis which includes normality test, homogeneity test, and hypothesis testing with t test. Based on the results of the research that has been carried out, it can be seen that there are significant differences in the inquiry learning model towards HOTS for fourth grade students of MIN 2 Ponorogo. This is proven by Tcount > Ttable (3.070 > 2.021) and the significance value of the two variables is less than 0.05 (t-tailed) 0.000 <0.05.